2011
DOI: 10.4049/jimmunol.1002860
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Resistance to Regulation by IL-4 during Th17 Maturation

Abstract: Th17 cells are highly pathogenic in a variety of immune-mediated diseases, and a thorough understanding of the mechanisms of cytokine-mediated suppression of Th17 cells has great therapeutic potential. In this report, we characterize the regulation of both in vitro- and in vivo-derived Th17 cells by IL-4. We demonstrate that IL-4 suppresses re-activation of committed Th17 cells, even in the presence of TGFβ, IL-6 and IL-23. Down-regulation of IL-17 by IL-4 is dependent on STAT6 and mediated by inhibition of ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…Because in vitro and in vivo studies have shown that the Th2 cytokines IL-4 and IL-13 downregulate Th17 cellular expression of IL-17A (14,(16)(17)(18) and because IL-17 signaling is critical for airway neutrophilia and bacterial clearance in response to K. pneumoniae (6), we hypothesized that (i) preexisting allergic airway inflammation decreases lung IL-17A expression in response to acute bacterial infection and (ii) decreased lung IL-17A expression results in impaired neutrophil recruitment to the airways, decreased lung bacterial clearance, and an increased lung bacterial burden. To test these hypotheses, we developed a model of preexisting allergic airway inflammation, induced by OVA sensitization and challenge, followed by acute lung bacterial infection with K. pneumoniae (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because in vitro and in vivo studies have shown that the Th2 cytokines IL-4 and IL-13 downregulate Th17 cellular expression of IL-17A (14,(16)(17)(18) and because IL-17 signaling is critical for airway neutrophilia and bacterial clearance in response to K. pneumoniae (6), we hypothesized that (i) preexisting allergic airway inflammation decreases lung IL-17A expression in response to acute bacterial infection and (ii) decreased lung IL-17A expression results in impaired neutrophil recruitment to the airways, decreased lung bacterial clearance, and an increased lung bacterial burden. To test these hypotheses, we developed a model of preexisting allergic airway inflammation, induced by OVA sensitization and challenge, followed by acute lung bacterial infection with K. pneumoniae (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic features of this allergic asthma phenotype include goblet cell metaplasia and mucus hypersecretion, airway hyperreactivity, smooth muscle hyperplasia, and airway eosinophilia (13). We and others have previously shown that the Th2 cytokines IL-4 and IL-13 negatively regulate IL-17A expression by Th17 cells (14)(15)(16)(17)(18). However, the ability of IL-4 and IL-13 to impair IL-17-dependent antibacterial immunity in the lung is not known.…”
mentioning
confidence: 99%
“…Studies from our group and others have established that STAT6 negatively regulates IL-17A expression in Th17 cells (9)(10)(11)(12)(13). By extension, we hypothesized that STAT6 also inhibits innate ␥␦17 cell cytokine secretion.…”
mentioning
confidence: 83%
“…While IL-4 neutralization with antibodies promotes IL-17A production by CD4 + T cells, exogenous IL-4 suppresses IL-17A expression [19,20]. IL-4 also suppresses IL-17F production from recently committed Th17 cells in a STAT6-dependent manner [21]. The antagonistic role of IL-4 on IL-17 is further underlined by studies using transcription factor-deficient mice.…”
Section: Silencing Th17-dominated Skin Inflammation By Il-4mentioning
confidence: 99%